GNSS interference detection, classification and localization using Software-Defined Radio - Bartl, Sascha; Berglez, Philipp; Hofmann-Wellenhof, Bernhard (2017 European Navigation Conference (ENC), 2017)
This paper presents details about the theoretical background as well as implementation of a GNSS interference monitoring system that can be used to continually monitor the GNSS frequency bands and thus alert users depending on the reliability of GNSS measurements. As shown in the results section, events of intentional GNSS interference are successfully detected and the system can also be used to classify different types of interference as well as localize the source of the disturbing signals.